ANALISIS MAKNA PROPERTI TARI JEPIN PIRING DI KERATON PAKUNEGARA KESUMA KECAMATAN TAYAN KABUPATEN SANGGAU - Putri, Indah Risa; Ismunandar, Ismunandar; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractÂ This study aimed to determine the shape of the property of the plate as well as the shape and shape of the property of the plate and the shape of the shape on the Jepin Piring dance. The method used in this research was descriptive method. The results of this study were in analyzing the meaning of Jepin Piring dance property, namely a meeting with informants who were stakeholders, King to thirteen Pakunegara Kesuma Palace and Jepin Piring dance dancer. Analyze the shape and meaning of Jepin Piring dance through interviews with informants and document it. The form of Jepin Piring dance property was a circular plate shape and a 7-shape flower shape such as jasmine flower, melur flower, kenanga flower, sweet night flower, yellow kantil flower, king flower, and hibiscus. The meaning of the shape of a circular plate and the white meaning of the plate. The meaning of shape and color in each flower was 7 shapes.Keywords : Dance Property, Jepin Piring, Meaning